Callus induction through Anther and Ovary of Kenaf (Hibiscus cannabinus L.) - Ahmed Mahmood Ibrahim; Fatimah Kayat; Dwi Susanto; Mohammed Ariffulah; Pedram Kashiani (Universiti Malaysia Kelantan, 2015)
In this research new protocol has been developed that would induce callus from anther and ovary of Kenaf. The haploid technique is a fast and efficient tool for developing new varieties in a comparatively short time. The present study was carried out to investigate the effect of cold treatment, plant growth regulators (PGR) and culture condition on callus induction from Kenaf anther and ovary culture. Kenaf HF992 cultivar was chosen as an explants material, several trails were carried out to investigate the Androgenesis and gynogenesis ability before we succeed to get high percentage of callus. Flower buds at the appropriate stage of anther and ovary development were sterilized and the anthers and ovary were carefully excised from the flowers and underwent to various pretreatments and inoculated into media contained different combinations of PGR like NAA(anaphthaleneacetic acid), BAP(N6-benzyladenine), 2iP(N6-(2-Isopentenyl) adenine) and TDZ (Thidiazuron)and kept in the dark place for different periods before transferred to light conditions. The best callus induction frequency from anther was 90.00 % in the optimized MS medium fortified with 3.0 mg/l 2iP + 3.0 mg/l NAA at the stage the microspores were at the uninucleate stage and the anther was about 7±1 mm long collected. And the best callus induction frequency from ovary was 91.25% in the optimized semi solid MS medium fortified with 3.0 mg/l 2iP + 3.0 mg/l NAA, and the flower buds was about 24±1 mm length which was collected 3-5 weeks after flower initiation. The effect of culture condition was highly significant, the root induction was highest (83.75% & 87.50%) of anther and ovary respectively when it kept in dark place for 28 days.